Structure, Anticorrosion and Antibacterial Evaluation of 1-(Morpholinomethyl)indoline-2,3-dione - Sun, Guo-Xin; Miao, Yan-Qing (Asian Journal of Chemistry, 2014)
In this paper, 3-(4-hydroxyphenylimino)indolin-2-one, was synthesized and analyzed by NMR, MS and X-ray single crystal analysis. The inhibition and the mechanism of the compound on the corrosion of high protective Q235A steel in HCl solution were screened and discussed. The results indicated that it can inhibit the corrosion with moderate inhibition efficiency in different conditions and the inhibition mechanism of the corrosion inhibiting may be mainly contributed to the adsorption. It was screened for antibacterial activity against oilfield water-borne bacteria and it showed good to moderate activity against sulfate reducing bacteria.